Patterns and factors influencing oral anticoagulant prescription in people with atrial fibrillation and dementia: Results from UK primary care - Pajaree Mongkhon (2020)
© 2020 The British Pharmacological Society Aims: Oral anticoagulant (OAC) is recommended for preventing stroke in atrial fibrillation (AF). However, the OAC utilisation in AF patients with dementia or cognitive impairment (CI) is limited. This study aimed to examine the prevalence of OAC prescriptions in AF patients with dementia/CI and to identify factors associated with OAC treatment within 180 days after dementia/CI diagnosis. Methods: Using The Health Improvement Network database, the annual trends of OAC between 2000 and 2015 were calculated. Multivariable logistic regression was performed to identify factors associated with OAC treatment. Results: The prevalence rate of OAC prescriptions increased from 6.1% in 2000 to 45.9% in 2015. Among OAC users, the proportion of direct oral anticoagulants (DOACs) use increased significantly from 0.1% in 2011 to 33.8% in 2015 (P-trend < 0.001), while the proportion of vitamin K antagonist use decreased by 28.6% from 100% in 2000 to 71.4% in 2015 (P-trend < 0.001). In the multivariable analysis, younger age, very old age, female sex, higher Charlson Comorbidity Index, having a HAS-BLED score ≥3, a history of intracranial bleeding, falls and polypharmacy were significantly associated with lower odds of receiving OAC. Conclusions: In UK primary care, OAC use increased from 2000 to 2015 in AF patients with dementia/CI, with a substantial increase in use of DOACs. Characteristics related to frailty are associated with lower odds of OAC prescription. Given the increasing use of DOACs in patients with dementia/CI, further studies are needed to investigate the safety and effectiveness of DOACs in this important patient group.